2016
DOI: 10.18410/jebmh/2016/670
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Prevalence of Anxiety Related Disorders Among Adolescents in Rural Kerala

Abstract: BACKGROUNDAnxiety disorders are the most common psychiatric problem in school going children worldwide. OBJECTIVEThis study was done to find the prevalence and risk factors for anxiety disorders in adolescents in rural Kerala. METHODSA school based survey was done among children of 10 to 13 years using SCARED anxiety scale. Specific items in the SCARED scale were used to assess panic disorder, generalised anxiety disorder, separation anxiety disorder, social anxiety disorder and school avoidance, detailed asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…Similar to the current study, several studies have shown higher incidences in females than males. [ 25 26 28 ] This disparity might be present as a result of certain biological factors, hormonal factors as well as differences in experiences during childhood and adolescent. [ 29 ] In contrast to results seen with depression, maximum number of cases with anxiety (63.3%) were found in children studying in <8 th class.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the current study, several studies have shown higher incidences in females than males. [ 25 26 28 ] This disparity might be present as a result of certain biological factors, hormonal factors as well as differences in experiences during childhood and adolescent. [ 29 ] In contrast to results seen with depression, maximum number of cases with anxiety (63.3%) were found in children studying in <8 th class.…”
Section: Discussionmentioning
confidence: 99%
“…The pooled prevalence of anxiety disorders was found to be 26% (95% CI: 16–37%, I 2 = 97.82%). The prevalence of anxiety disorders ranged from 12.4% to 60% across the nine studies 20 , 22 , 26 , 35 , 50 , 51 , 56 , 67 , 72 .…”
Section: Resultsmentioning
confidence: 99%
“…Four studies reported the prevalence of generalised anxiety disorder, which ranged from 7.2% to 37.2% across the studies 51 , 56 , 67 , 72 . The pooled prevalence of generalised anxiety disorder was found to be 16% (95% CI: 7–28%, I 2 = 97.73%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mishra et al [8] estimated the prevalence of depression and anxiety disorder in rural and sub-urban areas of Uttar Pradesh to be 14.5% and 15% respectively, in the age group of 11-18 years. The prevalence of anxiety disorder was however found to be almost three times higher (45.6%) among children in rural Kerala in a study by Manuel et al [9] Also, Jha et al reported the prevalence of depression to be as high as 49.2% [10]. The Global Burden of Disease Study found idiopathic developmental intellectual disability to be most prevalent mental disorder (4.5%), although the prevalence of conduct disorder (0.8%), ADHD and Autism spectrum disorders (ASD) (0.4% each) was also significant.…”
Section: Introductionmentioning
confidence: 85%